Differing presynaptic contributions to LTP and associative learning in behaving mice - Madroñal, Noelia; Gruart, Agnes; Delgado-García, José M. (Frontiers in Behavioral Neuroscience, 2009)
The hippocampal CA3-CA1 synapse is an excellent experimental model for studying the interactions between short- and long-term plastic changes taking place following high-frequency stimulation (HFS) of Schaffer collaterals and during the acquisition and extinction of a classical eyeblink conditioning in behaving mice. Input/output curves and a full-range paired-pulse study enabled determining the optimal intensities and inter-stimulus intervals for evoking paired-pulse facilitation (PPF) or depression (PPD) at the CA3-CA1 synapse. Long-term potentiation (LTP) induced by HFS lasted ≈ 10 days. HFS-induced LTP evoked an initial depression of basal PPF. Recovery of PPF baseline values was a steady and progressive process lasting ≈ 20 days, i.e., longer than the total duration of the LTP. In a subsequent series of experiments, we checked whether PPF was affected similarly during activity-dependent synaptic changes. Animals were conditioned using a trace paradigm, with a tone as a conditioned stimulus (CS) and an electrical shock to the trigeminal nerve as an unconditioned stimulus (US). A pair of pulses (40 ms interval) was presented to the Schaffer collateral-commissural pathway to evoke field EPSPs (fEPSPs) during the CS-US interval. Basal PPF decreased steadily across conditioning sessions (i.e., in the opposite direction to that during LTP), reaching a minimum value during the 10th conditioning session. Thus, LTP and classical eyeblink conditioning share some presynaptic mechanisms, but with an opposite evolution. Furthermore, PPF and PPD might play a homeostatic role during long-term plastic changes at the CA3-CA1 synapse.